Lead-induced gut injuries and the dietary protective strategies: A review. (August 2021) - Yu, Leilei; Yu, Yaqi; Xiao, Yue; Tian, Fengwei; Narbad, Arjan; Zhai, Qixiao; Chen, Wei
Graphical abstract: Highlights: Dietary Pb changes the proportions of gut bacteria and the microbial metabolisms. Dietary Pb increases the permeability of the gut barrier. Gut microbiota and gut barrier function affect Pb absorption and metabolism. Dietary strategies reduce Pb accumulation and alleviate Pb-induced gut dysbiosis. Abstract: Recently, a bidirectional relationship between dietary lead (Pb) exposure and gut changes has been identified. Pb causes gut dysbacteriosis and destroys gut physiological homeostasis, causing a series of oxidative stress, immune-inflammatory reactions and increased permeability of the intestinal barrier. Pb-induced gut dysbiosis and physiological disorders are related to impairments in nutrient absorption, essential element homeostasis, lipid metabolism, and nervous system, which can in turn influence Pb transport and metabolism. Dietary supplements such as probiotics, prebiotics, minerals, and antioxidants could be a potential strategy to alleviate Pb toxicity. They can protect the gut barrier, promote Pb discharge, and regulate oxidative stress and essential metal levels, which likely depend on the gut microbiota. Thus, dietary supplements, especially probiotics and prebiotics, are a new and safe strategy to prevent and alleviate Pb poisoning in the future.